GONZÁLEZ-TREVIJANO, Pedro: (2016). El purgatorio de las ideas Galaxia. Madrid: Gutemberg, Madrid (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2017)
Recensión de la obra; GONZÁLEZ-TREVIJANO, Pedro: (2016). El purgatorio de las ideas Galaxia. Madrid: Gutemberg, Madrid.